2022
DOI: 10.1021/acs.iecr.2c02519
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Complete Degradation of Metformin Using Vortex-Based Hydrodynamic Cavitation

Abstract: The present work successfully establishes the degradation of metformin, an antidiabetic drug, using vortex flow-based hydrodynamic cavitation (HC) and process intensification. Studies were carried out on a pilot plant (1 m 3 /h) and for high initial concentrations, 10−20 mg/L. Effects of intensifications using aeration and the addition of hydrogen peroxide on various process parameters were evaluated. A low degradation (3−5%) by HC at ΔP of 1 bar could be improved by process intensification using hydrogen pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The utilization of cavitation as a pre-treatment method is highly advantageous owing to its cost-effectiveness, absence of supplementary chemical usage, and absence of additional waste generation, as reported in previous studies [8]. Cavitation has demonstrated the effective degradation of various compounds, including phenol, dimethylformamide, magenta dye, 2-chlorophenol, methylene blue, triclosan, rhodamine B, octanol, cyclohexanol, and naproxen [17,18]. HC is deemed to possess superior energy efficiency and is frequently deemed appropriate for commercial-scale implementation and expansion.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The utilization of cavitation as a pre-treatment method is highly advantageous owing to its cost-effectiveness, absence of supplementary chemical usage, and absence of additional waste generation, as reported in previous studies [8]. Cavitation has demonstrated the effective degradation of various compounds, including phenol, dimethylformamide, magenta dye, 2-chlorophenol, methylene blue, triclosan, rhodamine B, octanol, cyclohexanol, and naproxen [17,18]. HC is deemed to possess superior energy efficiency and is frequently deemed appropriate for commercial-scale implementation and expansion.…”
Section: Introductionmentioning
confidence: 89%
“…The venturi configuration is frequently utilized in processes characterized by lower intensity, typically requiring pressures ranging from 15 to 20 bar [44,45], and involving physical transformations. In contrast, the utilization of the orifice flow configuration is commonly observed in the context of more intense chemical reactions [17,46]. However, a research investigation in the field of disinfection against pathogenic microorganisms has demonstrated that venturi-type reactors demonstrate enhanced efficacy in comparison to orifice plates [47].…”
Section: Geometry Of Hydrodynamic Cavitationmentioning
confidence: 99%
See 3 more Smart Citations